The Royal line of succession - Montague-Smith, Patrick W. (Andover : Pitkin Pictorials, 1993)
The British monarchy from Cerdic AD 534 to Queen Elisabeth II - The continuity of Kingship - The house of Cerdic - The house of Cerdic & Denmark - The house of Normandy, Blois and Anjou - The house of Anjou - The house of Tudor - The house of Stuart & Orange - The house of Hanover - The house of Saxe-Coburg & Gotha - The house of Windsor - The kings of Scotland - Sovereign princes of Wales - The kings of Ireland